Abordagens do documento audiovisual no campo teórico da arquivologia - Silva, Luiz Antonio Santana da [UNESP] (2013)
The audiovisual records’ need to be recognized as archival records is a result of the new documentary genre and mediums’ evolution which began being used for recording information, integrating the organic records groups. Besides, because of the close-to-real characteristics that the audiovisual language brings about, the institutions and people have been chosen such documentary genre to register their activities, once some information is better disclosed through this language. Thus, during throughout this investigation, through of the theoretical discussion, we could objectively look over the inserting the audiovisual records on archives, as well as the development of appointments to the adequate dealing with these records still on their primary value. Furthering this approach, we have been out to show and discuss the first questions raised by the main theorists and international conferences of the field, found on XI International Congress of Archives’ Annual came out in 1988, regarding of audiovisual records and, consequently, understanding the conflicts concerning such documents in archival environment. We have approached the existence disagreement on audiovisual records’ concept, pointing out the special records or audiovisual archival groups’ designation for such documents inside of Archival Institutions. We have also worked with the archival records and record group’s concepts in order to characterize the audiovisual record in such a manner and; finally, we have discussed means of information organization on audiovisual records, beginning by the use of the archival functions already applicable to current records. Thereby, this essay has proposed to approach central questions from Archival Science regarding the documental dealing towards the audiovisual genre’s archival records. Such questions and... (Complete abstract click electronic access below)